Optimizing early-phase immunotherapy trials: the role of biomarker enrichment strategies - Catani, Greta; Morchón-Araujo, Daniel; Mirallas, Oriol; Sánchez-Pérez, Vicky; Nuciforo, Paolo; Villacampa, Guillermo; Dienstmann, Rodrigo; Vivancos, Ana; Garralda, Elena; Hernando-Calvo, Alberto (Frontiers in Immunology, 2025)
Immune checkpoint inhibitors have revolutionized the treatment of solid tumors; however, their clinical efficacy remains limited to a subset of patients. Novel immunotherapy agents are being investigated in phase I clinical trials, with an increasing focus on biomarker selection strategies to optimize patient outcomes. Prior evidence suggests that biomarker-selected tumors may have better outcomes when treated with molecularly-guided therapies. However, the high complexity of tumor-host interactions and inter-patient variability indicates that a one-size-fits-all biomarker approach is unlikely to be sufficient in the immunotherapy landscape. This review highlights current biomarker-enrichment strategies in immunotherapy early drug development, addressing challenges and potential future directions for their effective implementation.